2002
DOI: 10.1111/j.1151-2916.2002.tb00066.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microstructure on the Thermal Conductivity of Hot‐Pressed Silicon Nitride Materials

Abstract: Si 3 N 4 materials with distinct microstructures were prepared by hot-pressing, varying the holding time at the maximum temperature, and using different types and amounts of sintering additives. Materials with thermal conductivities of 15-82 W⅐(m⅐K) ؊1 were obtained by changing the processing variables. The highest conductivity was measured for the material with the coarsest microstructure. The effect of microstructural parameters, such as percentage of secondary phases, grain size, and texture on thermal prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Also, the lower amount of secondary phase has a contribution to the higher thermal conductivity of the former. Some authors 2,6,17 revealed that the thermal conductivity of Si 3 N 4 ceramics complies with a rule of mixture composed of large grains of high conductivity and small matrix grains of low conductivity. This rule indicates that the thermal conductivity increases with the increase of the percentage of large grains.…”
Section: (2) Thermal Diffusivity/conductivitymentioning
confidence: 85%
“…Also, the lower amount of secondary phase has a contribution to the higher thermal conductivity of the former. Some authors 2,6,17 revealed that the thermal conductivity of Si 3 N 4 ceramics complies with a rule of mixture composed of large grains of high conductivity and small matrix grains of low conductivity. This rule indicates that the thermal conductivity increases with the increase of the percentage of large grains.…”
Section: (2) Thermal Diffusivity/conductivitymentioning
confidence: 85%
“…Textured β-Si 3 N 4 ceramics exhibit an interesting thermal anisotropy: the thermal conductivity is higher in the direction of the elongated grain alignment than in the direction perpendicular to the grain alignment [39,45,47,52,53,58,59,62,65,72]. Thus, texturing has become another important method for improving the thermal conductivity of β-Si 3 N 4 ceramics.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…Using a more refractory additive composition (Lu 2 O 3 -SiO 2 ), Zeng et al [72] reported the formation of textured Si 3 N 4 exhibiting a bending strength of ≈740 MPa at both room temperature (RT) and 1500 • C along the direction perpendicular to the grain alignment, that is, no strength degradation occurs even at 1500 • C, indicating better HT strength retention than that of untextured materials. Moreover, textured Si 3 N 4 exhibits unique anisotropic thermal conductivity [39,45,47,52,53,58,59,62,65,72], tribological and wear properties [54,55,63,66] and erosion behavior [67,69]. For example, Watari et al [52] showed that thermal conductivities of 155 and 52 Wm −1 K −1 could be achieved in highly textured Si 3 N 4 ceramic along the directions parallel and perpendicular to the grain alignment, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, we chose the Maxwell–Eucken relation to calculate the effective thermal conductivity of highly porous Si 3 N 4 foam, because it has been successfully by many researchers . The Maxwell–Eucken relation can be expressed as following:λ=λsλp+2λs+2νp(normalλpnormalλs)λp+2λsnormalν(normalλpnormalλs) where λ, λ s , and λ p are the thermal conductivity of porous material, thermal conductivity of solid phase, thermal conductivity of the pore (namely air), respectively. In addition, ν p is the porosity of the porous material.…”
Section: Resultsmentioning
confidence: 99%